Home Care: uma análise das decisões colegiadas do Tribunal de Justiça de Pernambuco. - Silva, José Marcio Carvalho da (2023)
This study is inserted in the concentration area of Law, Process and Citizenship, in the research line of “Process, hermeneutics and effectiveness of Rights” of PPGD/Unicap. It aims to analyze the collegiate judgments of the Court of Justice of Pernambuco (TJPE) published in the 2021-2022 biennium, referring to the home care, where the health insurance were at the active or passive poles. This study is justified by the persistent legal demand caused by successive denials of home care by health insurance, even though the TJPE has binding precedents that guarantee coverage of the procedure in the State of Pernambuco. Nevertheless, this study seeks to understand the foundations and justifications of the magistrates in their decisions and whether the TJPE precedents related to the subject are used. The literature review contemplates the aspects that characterize the scenario of the health rights in Brazil, more specifically the supplementary health services and their regulation, the phenomenon of the judicialization of health and aspects related to home care, including in the legal scope. The study is of the documentary type and uses an empirical-descriptive methodology with an analysis anchored in documental research and in legislative, jurisprudential and technical texts, with a focus on those related to the health and consumer rights. The search for judgments was carried out on the TJPE website using specific filters for the purpose of the study. From the 23 collegiate judgments rescued in the search, it was possible to synthesize and analyze what were the main reasons that led the beneficiaries of the health operators to activate the Justice Power, as well as the arguments brought by the health insurance to reject the home care and the grounds judges in their decisions. The results of this study indicate that although health insurance present arguments to deny the authorization of home care, the collegiate judgments of the TJPE between 2021 and 2022 are in line with the court's precedents and support the coverage of the procedure to beneficiaries.